Early-age fatigue damage assessment of cement-treated bases under repetitive heavy traffic loading - Arooran Sounthararajah (2018)
© 2018 American Society of Civil Engineers. This paper aims to develop measures to minimize the early-age fatigue damage of prematurely opened cement-treated bases (CTBs) due to repetitive heavy traffic loading. The four-point bending test was used in this study to characterize the early-age fatigue performance as well as the flexural properties of two different locally sourced granular materials stabilized with 3% general purpose (GP) cement. All the flexural tests were executed under stress-controlled mode. The fatigue test results evinced the existence of an endurance limit in cemented granular materials (CGMs) even at 7 days curing age. A stress-based fatigue performance model was developed for predicting the early-age fatigue performance of CGMs in service. In addition, the 7-day fatigue test data from this study were validated using existing CGM fatigue models. The numerical results obtained from the CIRCLY program indicated that the level of interaction between the axles of an axle configuration decreases with decreasing CTB layer thickness, resulting in increased pavement fatigue damage. It was also found that the asphalt cover over CTB required to prevent the occurrence of initial fatigue damage to the CTB decreases with increasing CTB modulus, subgrade strength, and CTB layer thickness. The limitations and simplifications in current pavement design and testing methods are also critically discussed and addressed on the basis of the results of this study.